Design drawing - Francis D. K. Ching; Steven P. Juroszek (Hoboken, New Jersey : Wiley, 2018)
"Sales handles - In Frank's distinctive graphic style, over 1500 hand drawings reinforce the concepts and lessons of each chapter - Expanded to include new exercises and examples that range in complexity - Features all-new digital drawing topics, such as, digital elevations and fabrication, hybrid floor plans, and hand to digital fluency - Includes access to a brand new website featuring videos of the author demonstrating freehand techniques in a step-by-step manner in studio and on location. Readers will gain a greater appreciation of the techniques presented in the book through the power of animation, video, and 3D models. Market description (Please include secondary markets) Students of Architecture, Interior Design, Landscape Architecture, and the Fine Arts (appropriate for use in focused drawing courses, or in Design Studio courses where drawing is an important component), Design Professionals who are interested in honing their design drawing skills"--
Keywords: ARCHITECTURE / Design, Drafting, Drawing & Presentation